Mitigasi Risiko Bencana Alam dan Non-Alam Berbasis Komunitas melalui Pemasangan Jaring Sampah dan Rambu Keselamatan di Lingkungan Kelurahan Srengsem - Viona Finanda; Muhammad Raden Recza Bijaksana; Muhammad Farid Saputra (FT Universitas Lampung, 2026)
The potential for flooding caused by clogged drainage channels and the risk of accidents on steep roads are problems faced by Srengsem Village, Panjang District, Bandar Lampung City. This activity aims to improve disaster and non-disaster mitigation efforts through the installation of trash nets and safety signs. The method used is descriptive qualitative with a participatory approach through observation, interviews, and documentation involving the community and local authorities. The results show that the installation of trash nets helps collect waste carried by water, making it easier for residents to clean the drainage and reduce the potential for flooding. Meanwhile, the installation of safety signs increases public awareness of steep, slippery, and landslide-prone roads. This activity contributes to strengthening community participation and increasing environmental safety.